Perceptions of Indian Students Towards Bullying; Intervention Through Bullying Intervention Module (BIM) - Shweta Singh; Seema Singh (SAGE Open)
Bullying, a pernicious affliction that indiscriminately afflicts students of all ages and backgrounds, is a scourge that demands our attention. It involves a pattern of conduct whereby one individual is repeatedly targeted for aggression by one or more others, often due to a power imbalance. In response to this pressing issue, the present study endeavored to address bullying among secondary-level students by implementing a Bullying Intervention Module, while also seeking to explore the root causes and consequences of such behavior. The module, which was designed to raise awareness, promote self-reflection, and foster a commitment to new behaviors, was developed with great care and attention to detail. This study was conducted using a mixed-method approach that combined qualitative and quantitative methods. In the quantitative phase of the study, a quasi-experimental pre-test and posttest with a control group design were employed, with a total of 60 students from class 9th, selected purposively. The findings revealed that the intervention had a significant impact on students’ awareness and behavior in relation to bullying. In the qualitative phase of the study, a semi-structured interview schedule was utilized. The results showed that students perceived financial condition, physical appearance, being different from others, enjoyment, violence, revenge, power, and social media use as major causes of bullying, with the consequences including school absenteeism, drop-outs, low academic achievement, anxiety, stress, depression, shyness, aggression, loneliness, and even suicide.